Dimensi Dan Struktur IPS - Eka Yusnaldi; Chairunnisa Wardani; Nazzwa Adelia Putri; Husnatun Leony Harahap; Salwa Ramadani Dongoran; Aurora Zywetta; Imam Fahman Syah Nainggolan (Journal on Education, 2024)
Social Sciences (IPS) is a broad and complex field of study involves understanding various aspects of human society. In In this abstract, we explore the dimensions and fundamental structure of the IPS become the basis for understanding social phenomena. Dimensions of Social Sciences covers three main aspects. First, IPS is an interdisciplinary scientific discipline, combines perspectives and methodologies from a number of fields such as history, geography, sociology, economics, and politics. Second, IPS is contextual, where the analysis always considers historical, cultural, political and economic context where social phenomena take place. Third, IPS is reflective and encouraging critical thinking about values, norms, and power structures forming society. The structure of social studies can be analyzed at three levels. Level Micro examines individual interactions in small contexts such as family, friends, or work environment. The meso level is concerned with the larger social structure such as organizations, institutions and local communities. Meanwhile at the macro level observing social patterns involving large entities such as countries, economies global, or conflict between nations. Deep understanding of the dimensions and IPS structure has important implications in various aspects of human life,including policy formation, development of development strategies, and resolution of social conflicts. Using this conceptual framework, para IPS researchers and practitioners can make significant contributions in solvingcomplex social challenges and creating a more just and fair society sustainable.